Increasing public knowledge regarding the dangers and impacts of smoking through education - Sofiana, Liena; Rosita, Diah Ayu; Zulkarnain, Ahmad Aditya Sidik; Widiantika, Maradella; Zafirah, Kamilah; Safitri, Diah; Fauzi, Amir (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
Smoking behavior is still a health problem globally and in Indonesia. Smoking is a behavior that is a risk factor for various types of non-communicable diseases. Based on the results of community diagnosis, smoking behavior at home is 27%, and this includes groups of men and teenagers. Based on this problem, education is needed about the dangers of smoking through community service activities. This activity aims to provide an understanding of the dangers and impacts of smoking. The method used is direct counseling, assisted by leaflets and posters so they can be read again at home. The results obtained were an increase in knowledge before and after being given counseling regarding the dangers and impacts of smoking (sig. 0.000). It can be concluded that education about the dangers and impacts of smoking is effective in increasing public knowledge, so it is hoped that this understanding can influence smoking cessation behavior.